Adaptation and Natural Selection : A Critique of Some Current Evolutionary Thought - Williams, George C. (George Christopher), 1926-2010 (Book collections on Project MUSE., 2019)
Biological evolution is a fact-but the many conflicting theories of evolution remain controversial even today. When Adaptation and Natural Selection was first published in 1966, it struck a powerful blow against those who argued for the concept of group selection-the idea that evolution acts to select entire species rather than individuals. Williams's famous work in favor of simple Darwinism over group selection has become a classic of science literature, valued for its thorough and convincing argument and its relevance to many fields outside of biology. Now with a new foreword by Richard Dawkins, Adaptation and Natural Selection is an essential text for understanding the nature of scientific debate.